ANALISA EFISIENSI THERMAL BOILER TIPE CIRCULATION FLUIDIZED BED DI PLTU 3x10MW - Jihan Syalsabila; Hendradinata , Hendradinata; Fenoria Putri; Safe’i, Safe’i; Siproni, Siproni; HB, Indra (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The need for electrical energy is increasing with economic growth. One of the government's efforts to increase electricity production is with the existence of Steam Power Plants. Boiler or steam generator a tool utilized to generate steam which consists of two important components, namely a heating system to generate heat from burning fuel and a system that converts water into steam. The percentage of boiler performance is the percentage of energy absorbed by the steam boiler with fuel input energy. Boiler performance greatly affects the performance of a PLTU where the use of fuel affects the steam produced. This research was carried out using the direct method by taking daily boiler log sheet data for 2 months, namely April and May, using coal calorific values, namely 5615 kcal/kg and 5654 kcal/kg. The results, the highest boiler efficiency was 55.95% with a calorific value of 5654 coal while the lowest boiler efficiency was 36.29% with a calorific value of 5615 kcal/kg. From the results obtained, it can be concluded that the steam flow rate is not constant and the excessive use of fuel causes boiler efficiency to experience conditions that are not optimal. The calorific value of coal is affected by the water content contained in the coal. The higher the water content, the more energy is required for the coal burning process.